067. Report in Delayed Peritonitis Due to Ileal Perforation Due to Abdominal Blunt Trauma in Sardjito Hospital - Haqim, Rijal Maulana; Nirbira, Alam; Setyawan, Nurcahya (JBN (Jurnal Bedah Nasional); Vol 8 No 2 (2024): Proceeding The 2nd National Conference of Indonesia Surgical Education, 2024)
Background : Abdominal blunt trauma is a difficult situation, leading to considerable illness and death, particularly in developing nations. The later appearance of symptoms and indicators in these individuals significantly adds to the heightened illness and death rates experienced by the patients. Small bowel perforation following blunt abdominal trauma is an uncommon occurrence, and typically, such cases manifest right after the trauma. Case : We present one case of elderly patient with ileum perforation with Boey Score 2 who showed symptoms on the second day after the injury. We performed ileostomy on the perforation site. We found duodenal perforation 1.5 cm in diameter and 20 cm from ileocecal junction. We refreshed the perforation edge. Patient was in hospital for 5 days and before being discharged. Conclusion: Small bowel perforation is rare, leading to a delay in definitive treatment. Gathering a detailed injury mechanism, observing the patient, conducting thorough investigations using CT and/or FAST, and remaining aware of the potential for small bowel perforation are crucial for successful management of patients with blunt abdominal trauma.